C1QTNF3 is Upregulated During Subcutaneous Adipose Tissue Remodeling and Stimulates Macrophage Chemotaxis and M1-Like Polarization - Micallef, Peter; Vujičić, Milica; Wu, Yanling; Peris, Eduard; Wang, Ying; Chanclón, Belén; Ståhlberg, Anders; Cardell, Susanna L.; Wernstedt Asterholm, Ingrid (Frontiers in Immunology, 2022)
The adipose tissue undergoes substantial tissue remodeling during weight gain-induced expansion as well as in response to the mechanical and immunological stresses from a growing tumor. We identified the C1q/TNF-related protein family member C1qtnf3 as one of the most upregulated genes that encode secreted proteins in tumor-associated inguinal adipose tissue - especially in high fat diet-induced obese mice that displayed 3-fold larger tumors than their lean controls. Interestingly, inguinal adipose tissue C1qtnf3 was co-regulated with several macrophage markers and chemokines and was primarily expressed in fibroblasts while only low levels were detected in adipocytes and macrophages. Administration of C1QTNF3 neutralizing antibodies inhibited macrophage accumulation in tumor-associated inguinal adipose tissue while tumor growth was unaffected. In line with this finding, C1QTNF3 exerted chemotactic actions on both M1- and M2-polarized macrophages in vitro. Moreover, C1QTNF3 treatment of M2-type macrophages stimulated the ERK and Akt pathway associated with increased M1-like polarization as judged by increased expression of M1-macrophage markers, increased production of nitric oxide, reduced oxygen consumption and increased glycolysis. Based on these results, we propose that macrophages are recruited to adipose tissue sites with increased C1QTNF3 production. However, the impact of the immunomodulatory effects of C1QTNF3 in adipose tissue remodeling warrants future investigations.